2021
DOI: 10.3389/fcvm.2021.711465
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide Post-conditioning Activates the HIF-1/HRE Pathway to Induce Myocardial Protection in Hypoxic/Reoxygenated Cardiomyocytes

Abstract: Background: Previous studies have shown that diazoxide can protect against myocardial ischemia-reperfusion injury (MIRI). The intranuclear hypoxia-inducible factor-1 (HIF-1)/hypoxia-response element (HRE) pathway has been shown to withstand cellular damage caused by MIRI. It remains unclear whether diazoxide post-conditioning is correlated with the HIF-1/HRE pathway in protective effect on cardiomyocytes.Methods: An isolated cardiomyocyte model of hypoxia-reoxygenation injury was established. Prior to reoxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In this study, diazoxide postconditioning was found to significantly reduce myocardial ischemia-reperfusion injury, which is consistent with our previous results ( Cao et al, 2015 ; Pan et al, 2020 ; Chen et al, 2021 ). The present study indicated that MIRI disturbed multiple metabolic changes, including decreased levels of citrate, nicotinate, L-threonine, and L-lysine.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, diazoxide postconditioning was found to significantly reduce myocardial ischemia-reperfusion injury, which is consistent with our previous results ( Cao et al, 2015 ; Pan et al, 2020 ; Chen et al, 2021 ). The present study indicated that MIRI disturbed multiple metabolic changes, including decreased levels of citrate, nicotinate, L-threonine, and L-lysine.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence indicates that inhibiting SDH reduces the content of succinate and ROS production, thus protecting cardiac function from MIRI ( Valls-Lacalle et al, 2018 ; Xu et al, 2018 ). Our previous result showed that diazoxide postconditioning can decrease ROS level ( Chen et al, 2021 ). This study showed that the level of succinate decreased after diazoxide postconditioning, which may be involved in inhibiting SDH ( Anastacio et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the HIF-1α/BNIP3-mediated regulation of mitophagy that we have discovered provides new insights into potential therapeutic targets for myocardial ischemia–reperfusion injury [ 69 ]. A growing body of scholars has begun to direct their attention towards the role of autophagy in myocardial protection, holding the promise of unveiling novel therapeutic strategies for MIRI [ 70 ].…”
Section: Discussionmentioning
confidence: 99%